Thelocarpon intermediellum Nyl. - a new for Ukraine species of lichens (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Thelocarpon intermediellum Nyl. (Acarosporaceae, Lecanorales) is firstly reported for Ukraine from Slavyanoserbs`kiy district in Lugans`ka oblast. It is collected on concrete stone in steppe on territory of the former Tryohizbenskiy military area. The notes about Thelocarpon laureri (Flot.) Nyl. as a new for steppe zone and for Crimean peninsula are provided. The key for Ukrainian Thelocarpon is given.
Keywords: Thelocarpon, Khersons`ka oblast, Mykolaivska oblast, Lugans`ka oblas,t AR Crimea, Ukraine.